Insights into the pH-driven emulsifying properties and self-assembly behaviour of pea peptides - Xiaoyang Sun; Yan Chen; Xinxin Xu; Pei Wang; Jinhu Tian; Meichen Liu; Xiufeng Zhang; Xiaoqing Yuan; Fusheng Chen; Lifen Zhang (Food Research International, 2026)

Unveiling the landscape of BPS derivatives in urine from eastern and western Chinese population - Qingqing Zhu; Meichen Lu; Xueyu Weng; Yitong Pan; Xianping Wei; Longyao Xu; Yifan Li; Chunyang Liao; Guibin Jiang (Environmental Research, 2026)

Temperature-responsive carbon dots-spiropyran photochromic films for stepwise-decryption optical anti-counterfeiting with information self-destruction - Meichen Meng; Zhimeng Ma; Mingbo Yue; Chang Liu; Xiaoyu Xu; Qiang Fu (Chemical Engineering Journal, 2026)

Machine learning with augmented data for predicting bentonite swelling pressure - Wenyan Shi; Feng Zhang; Changdong Li; Qingbing Liu; Long Xu; Zhangrong Liu; Hangjing Zhou; Meichen Liu; Yuxian Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Rapid fractionation of moso bamboo using ternary deep eutectic solvent for integrated enzymatic hydrolysis and in situ treatment liquid gelation - Jiaying Li; Chengcheng Yuan; Meichen Zhang; Yingchao Wang; Feng Xu; Fengshan Zhang; Zongwei Guo; Hao Ma; Xingxiang Ji (Chemical Engineering Journal, 2026)

Decoupling of arbuscular mycorrhizal fungi and soil organic carbon under nitrogen addition in terrestrial ecosystems: a meta-analysis - Andi Li; Jing Chen; Senhao Wang; Guangcan Yu; Meichen Xu; Anchi Wu; Jinhua Mao; Wei Zhang; Zhanfeng Liu; Juxiu Liu; Jiangming Mo; Mianhai Zheng (Frontiers of Earth Science, 2026)

Predicting the toxicity of organic chemicals to Tetrahymena pyriformis based on machine learning and interpretable models - Meichen Sun; Handong Yu; Caige Lu; Yue Wang; Minghui He; Dongmei Zheng; Xiaotian Xu; Limin Su; Yuanhui Zhao (Process Safety and Environmental Protection, 2026)

Chemical constituents from the fruits of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Wenjing Zu; Lu Guan; Jie Liu; Cai-Wen Meng; Hongyun Bai; MeiChen Li; Jianyu Liu; Yongnan Xu (Biochemical Systematics and Ecology, 2026)

SiO2 NP promotes allergic gastritis induced by degranulation of mouse MC9 cell through AQP4-mediated impairment of SIRT3-TFAM deacetylation and mitochondrial autophagy - Yutian Lei; Xiaodan Wang; Hao Wu; Meichen Gao; Tong Xu; Hongjin Lin (Journal of Hazardous Materials, 2025)

Occurrence, transformation pathway, and toxicity of p-phenylenediamine antioxidants and their transformation products: A review and toxicity prediction - Meichen Sun; Meinuo Lv; Handong Yu; Zhijuan Cai; Minghui He; Xiaotian Xu; Limin Su; Yuanhui Zhao (Journal of Environmental Chemical Engineering, 2025)

Elucidating the occurrence patterns of Alternaria toxin tenuazonic acid in individual tomatoes through MALDI-MSI and LC-MS/MS - Fan Sun; Yingying Fan; Yingying Dai; Muhai Tang; Jiangtao Du; Anqi Xu; Meichen Liu; Qianqian Chu; Dianzhen Yu; Ye Tian; Xiyan Sun; Weiheng Ren; et al. (Food Chemistry, 2025)

Complexes of Dendrobium officinale anthocyanins and polysaccharides: Structural characteristics, stability, antioxidant properties, and bioavailability - Bowen Sui; Yanling Sun; Jingzhi Wang; Yuan Cui; Haibo Xu; Daqing Zhao; Meichen Liu; Zhengqi Dong; Siming Wang; Shichao Liu (Food Bioscience, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Pyrochar relieved the negative effects of hydrothermal pretreatment of sludge on vivianite production in anaerobic digestion - Yafei Cheng; Xiaofeng Xu; Yan Shi; Meichen Sun; Chao Zhang; Zhijian Shi; Yalei Zhang; Shicheng Zhang; Gang Luo (Chemical Engineering Journal, 2025)

Quercetin attenuates DEHP-induced pyroptosis and programmed necrosis in chicken duodenum through regulation of the TLR4/MyD88/NF-κB pathway - Ruirui Xie; Tong Xu; Yilin Yin; Meichen Liu; Chenxi Huang; Wenwen Zhang; Shu Li (Environmental Pollution, 2025)

mtNET-mineral complex: a building block of calculus - Yutong Fu; Meichen Wan; Yina Zhu; Dongxiao Hao; Qianqian Wan; Wen Niu; Zhaoyang Ren; Kehui Xu; Weijun Qin; Shiren Sun; Wei Yi; Kai Jiao; et al. (Science Bulletin, 2025)

Emamectin benzoate and nanoplastics induce PANoptosis of common carp (Cyprinus carpio) gill through MAPK pathway - Zhangyi Ju; Yanju Bi; Meichen Gao; Yilin Yin; Tong Xu; Shiwen Xu (Pesticide Biochemistry and Physiology, 2024)

Resveratrol alleviates Mono-2-ethylhexyl phthalate-induced mitophagy, ferroptosis, and immunological dysfunction in grass carp hepatocytes by regulating the Nrf2 pathway - Xiaodan Wang; Meichen Gao; Xiunan Lu; Yutian Lei; Jiatong Sun; Mengyao Ren; Tong Xu; Hongjin Lin (Journal of Environmental Management, 2024)

Photolysis of p-phenylenediamine rubber antioxidants in aqueous environment: Kinetics, pathways and their photo-induced toxicity - Chen Wang; Meichen Sun; Minghui He; Siyu Zhao; Meinuo Lv; Xiaotian Xu; Chunbei Ye; Linjing Li; Limin Su; Yuanhui Zhao (Journal of Hazardous Materials, 2024)

Quercetin attenuates SiO2-induced ZBP-1-mediated PANoptosis in mouse neuronal cells via the ROS/TLR4/NF-κb pathway - Meichen Liu; Meichen Gao; Xu Shi; Yilin Yin; Huanyi Liu; Ruirui Xie; Chenxi Huang; Wenwen Zhang; Shiwen Xu (Journal of Environmental Management, 2024)

Quercetin antagonizes apoptosis, autophagy and immune dysfunction induced by di(2-ethylhexyl) phthalate via ROS/ASK1/JNK pathway - Jiatong Sun; Xiaodan Wang; Tong Xu; Mengyao Ren; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Silicon dioxide particles induce DNA oxidative damage activating the AIM2-mediated PANoptosis in mice cerebellum - Hao Cai; Meichen Gao; Tong Xu; Ke Li; Yuanxin Zhou; Chencong Lyu; Shiwen Xu (Chemico-Biological Interactions, 2024)

Combined exposure of emamectin benzoate and microplastics induces tight junction disorder, immune disorder and inflammation in carp midgut via lysosome/ROS/ferroptosis pathway - Xu Shi; Tong Xu; Meichen Gao; Yanju Bi; Jiaqi Wang; Yilin Yin; Shiwen Xu (Water Research, 2024)

Effects of atrazine and curcumin exposure on TCMK-1 cells: Oxidative damage, pyroptosis and cell cycle arrest - Mengyao Ren; Xiunan Lv; Tong Xu; Jiatong Sun; Meichen Gao; Hongjin Lin (Food and Chemical Toxicology, 2024)

Zinc Inhibits Lead-Induced Oxidative Stress and Apoptosis of ST Cells Through ROS/PTEN/PI3K/AKT Axis - Haoyu Zhang; Kexin Sun; Meichen Gao; Shiwen Xu (Biological Trace Element Research, 2024)

Adsorption and removal of polystyrene nanoplastics from water by green-engineered clays - Meichen Wang; Kendall Lilly; Leisha M.A. Martin; Wei Xu; Phanourios Tamamis; Timothy D. Phillips (Water Research, 2024)

Long‐term nitrogen and phosphorus addition have stronger negative effects on microbial residual carbon in subsoils than topsoils in subtropical forests - Linjie Fan; Yuewei Xue; Donghai Wu; Meichen Xu; Andi Li; Baixin Zhang; Jiangming Mo; Mianhai Zheng (Global Change Biology, 2024)
Highly weathered lowland (sub)tropical forests are widely recognized as nitrogen (N)‐rich and phosphorus (P)‐poor, and the input of N and P affects soil carbon (C) cycling and storage in these ecosystems. Microbial residual C (MRC) plays a crucial role in regulating soil organic C (SOC) stability in forest soils. However, the effects of long‐term N and P addition on soil MRC across different soil layers remain unclear. This study conducted a 12‐year N and P addition experiment in two typical subtropical plantation forests dominated by Acacia auriculiformis and Eucalyptus urophylla trees, respectively. We measured plant C input (fine root biomass, fine root C, and litter C), microbial community structure, enzyme activity (C/N/P‐cycling enzymes), mineral properties, and MRC. Our results showed that continuous P addition reduced MRC in the subsoil (20–40 cm) of both plantations ( A. auriculiformis : 28.44% and E. urophylla : 28.29%), whereas no significant changes occurred in the topsoil (0–20 cm). N addition decreased MRC in the subsoil of E. urophylla (25.44%), but had no significant effects on A. auriculiformis . Combined N and P addition reduced MRC (34.63%) in the subsoil of A. auriculiformis but not in that of E. urophylla . The factors regulating MRC varied across soil layers. In the topsoil (0–10 cm), plant C input (the relative contributions to the total variance was 20%, hereafter) and mineral protection (47.2%) were dominant factors. In the soil layer of 10–20 cm, both microbial characteristics (41.3%) and mineral protection (32.3%) had substantial effects, whereas the deeper layer (20–40 cm) was predominantly regulated by microbial characteristics (37.9%) and mineral protection (18.8%). Understanding differential drivers of MRC across soil depth, particularly in deeper soil layers, is crucial for accurately predicting the stability and storage of SOC and its responses to chronic N enrichment and/or increased P limitation in (sub)tropical forests.

Eucalyptol ameliorates chlorpyrifos-induced necroptosis in grass carp liver cells by down-regulating ROS/NF-κB pathway - Naixi Yang; Jinming Guo; Hao Wu; Meichen Gao; Shiwen Xu (Pesticide Biochemistry and Physiology, 2024)

Sodium selenite (Na2SeO3) attenuates T-2 toxin-induced iron death in LMH cells through the ROS/PI3K/AKT/Nrf2 pathway - Xinrui Deng; Tingting Yu; Meichen Gao; Jiaqi Wang; Wenying Sun; Shiwen Xu (Food and Chemical Toxicology, 2023)

Selenium alleviates lead-induced CIK cells pyroptosis and inflammation through IRAK1/TAK1/IKK pathway - Xiunan Lv; Mengyao Ren; Tong Xu; Meichen Gao; Huanyi Liu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Association between arsenic (+3 oxidation state) methyltransferase gene polymorphisms and arsenic methylation capacity in rural residents of northern China: a cross-sectional study - Meichen Zhang; Haili Xu; Qun Lou; Zaihong Zhang; Xin Zhang; Fanshuo Yin; Man Lv; Ying Zhang; Yunyi Yin; Yanhui Gao; Xiaona Liu; Yanmei Yang (Archives of Toxicology, 2023)

Evodiamine alleviates DEHP-induced hepatocyte pyroptosis, necroptosis and immunosuppression in grass carp through ROS-regulated TLR4 / MyD88 / NF-κB pathway - Yutian Lei; Tong Xu; Wenying Sun; Xiaodan Wang; Meichen Gao; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Negative responses of terrestrial nitrogen fixation to nitrogen addition weaken across increased soil organic carbon levels - Mianhai Zheng; Meichen Xu; Dejun Li; Qi Deng; Jiangming Mo (Science of The Total Environment, 2023)

SIRT1/P53 pathway is involved in the Arsenic induced aerobic glycolysis in hepatocytes L-02 cells - Meichen Zhang; Zaihong Zhang; Qun Lou; Xin Zhang; Fanshuo Yin; Yunyi Yin; Haili Xu; Ying Zhang; Chenlu Fan; Yanhui Gao; Yanmei Yang (Environmental Science and Pollution Research, 2023)

Verniciflavanol A, a profisetinidin-type-4-arylflavan-3-ol from toxicodendron vernicifluum protects SH-SY5Y cells against H2O2-Induced oxidative stress - Meichen Li; Yunqiang Zhang; Tingting Han; Lu Guan; Dongxue Fan; Qinke Wu; Jianyu Liu; Yongnan Xu; Yanhua Fan (Phytochemistry, 2023)

ROS/ER stress contributes to trimethyltin chloride-mediated hepatotoxicity; Tea polyphenols alleviate apoptosis and immunosuppression - Huijun Zhu; Meichen Gao; Wenying Sun; Huanyi Liu; Shiwen Xu; Xiaojing Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Research for type 2 diabetes mellitus in endemic arsenism areas in central China: role of low level of arsenic exposure and KEAP1 rs11545829 polymorphism - Chenlu Fan; Zaihong Zhan; Xin Zhang; Qun Lou; Ning Guo; Mengyao Su; Yue Gao; Ming Qin; Liaowei Wu; Wei Huang; Meichen Zhang; Fanshuo Yin; et al. (Archives of Toxicology, 2022)

Isolation of a new monoterpenoid glycoside from Anhua dark tea based on an NMR-guided method and its cytotoxic activity against MDA-MB-231 and SH-SY5Y cell lines - Yunqiang Zhang; Jianyu Liu; Miao Chen; Yanhua Fan; Meichen Li; Andong Wang; Gaigai Liu; Yongnan Xu; Xuhong Ren; Yan Xiao (Natural Product Research, 2022)